Invasive Orbital Aspergillosis: Treatment Challenge. - Aktar , Sanjida; Sultana, Farjana; Haqueahsanul,; Rahim , Abdur; Islam, Mohammad Rafiqul (Bangladesh Journal of Medicine, 2024)
Orbital cellulitis is a serious infection that involves the muscle and fat located within the orbit. The causative organisms of orbital cellulitis are commonly bacterial but can also be polymicrobial, even fungal or mycobacteria. In immunocompromised patients with orbital cellulitis, mucormycosis and invasive aspergillosis should be considered as the cause of orbital cellulitis.A 55 years old, normotensive, non-diabetic lady came with swelling of left eye with purulent discharge, on October, 2022. She took consultation from an Ophthalmologist and had excision of the tissue mass. Her histological diagnosis was invasive orbital aspergillosis. After 2 months, she again developed orbital swelling with severe purulent discharge and consulted with department of Maxillofacial surgery. They referred the patient to us for proper management.On query, patient gave history of completing COVID-19 vaccination 2nd dose and couldn’t receive 3rd dose due to this medical condition. She did not have any history of diagnosed COVID-19 infection.After complete clinical evaluation, we decided to arrange FESS (functional endoscopic sinus surgery) with surgical debridement. After surgery, we planned to start Inj. Amphotericin-B. Considering patient’s poor financial condition, we started Tab. Posaconazole. During hospital stay for 3 months, she suffered from orbital infection twice. Culture sensitivity reports revealed Pseudomonas (1st time) and E. coli (2nd time). We treated the patient with antibiotics accordingly. She took Tab. Posaconazole for 6 months and was cured completely. In conclusion, high suspicion of fungal infection should be kept in mind even in absence of any co-morbidity. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 177